Two-Sided Platform Competition in a Sharing Economy - Zhang, Chenglong; Chen, Jianqing; Raghunathan, Srinivasan (Management Science, 2022)
We examine competition between two-sided platforms in a sharing economy. In sharing economies, workers self-schedule their supply based on the wage they receive. The platforms compete for workers as well as consumers. To attract workers, platforms use diverse wage schemes, including fixed commission rate, dynamic commission rate, and fixed wage. We develop a model to examine the impacts of the self-scheduled nature of the supply on competing platforms and the role of the wage scheme in the platform competition. We find that the price competition between platforms is more intense in a sharing economy compared with an economy with a fixed supply of workers if and only if the platforms serve more consumers and workers in the sharing economy than in the traditional economy, regardless of the wage scheme employed by the platforms. Further, any of the three wage schemes can be the best for the platforms and the worst for consumers and workers, depending on the market characteristics. In markets where the competition is more fierce on the demand side than on the supply side, the fixed-wage scheme results in the highest profits for the platforms and lowest surpluses for consumers and workers. In contrast, in markets where the competition on the supply side is more competitive, when the supply is highly (mildly) more competitive, the fixed-commission-rate (dynamic-commission-rate) scheme generates the highest profits for platforms, leading to the lowest surpluses for consumers and workers and the lowest social welfare. The differential impacts of the wage scheme on the price (demand side) and quantity (supply side) competition explain our findings. This paper was accepted by Kartik Hosanagar, information systems. Supplemental Material: The e-companion is available at https://doi.org/10.1287/mnsc.2022.4302 .